2016
DOI: 10.1016/j.spinee.2015.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Early magnetic resonance imaging biomarkers to predict local control after high dose stereotactic body radiotherapy for patients with sarcoma spine metastases

Abstract: Background Context Recent advances in image guidance and stereotactic body radiotherapy (SBRT) have resulted in unprecedented local control for spinal metastases of all histologies. However, little is known about early imaging biomarkers of local control. Purpose To identify early MRI biomarkers to predict local control after SBRT for patients with sarcoma spine metastases. Study Design/Setting Retrospective case series at a large tertiary cancer center. Patient Sample From 2011 to 2014, nine consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Recent studies have demonstrated that DCE-MRI can detect tumor response to high-dose RT in spinal bone metastases through changes in perfusion parameters shortly after treatment. 10 , 16 Here, we show that in addition to evaluating tumor response to treatment, DCE-MRI can predict local tumor recurrence following high-dose RT. Specifically, average change in perfusion parameters V p and K trans differed significantly from the LC group compared with the LR group ( P < .01).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recent studies have demonstrated that DCE-MRI can detect tumor response to high-dose RT in spinal bone metastases through changes in perfusion parameters shortly after treatment. 10 , 16 Here, we show that in addition to evaluating tumor response to treatment, DCE-MRI can predict local tumor recurrence following high-dose RT. Specifically, average change in perfusion parameters V p and K trans differed significantly from the LC group compared with the LR group ( P < .01).…”
Section: Discussionmentioning
confidence: 76%
“… 14 , 15 Furthermore, DCE-MRI has been used to assess treatment response in patients with spinal metastases treated with high-dose radiation therapy (RT). 10 , 16 It has been demonstrated that changes in perfusion parameters, particularly V p , reflect tumor response to RT in spinal bone metastases. 10 …”
Section: Introductionmentioning
confidence: 99%
“…A recent early stage breast cancer study [13] found significant increases in the initial area under an enhancement curve for the entire GTV at one-week post-single dose SABR. However, when assessing response at later times (>1month) in other cancer sites, decreases in K trans were associated with pathologically complete response [39][40][41]. Two of these reports [39,41] also indicated that decreases in rK trans was indicative of response.…”
Section: Discussionmentioning
confidence: 99%
“…Multiparametric MRI utilizing DCE information outperformed clinical radiologists' anatomical impressions of treatment outcomes. 43 In both radiation and specifically antiangiogenic systemic therapy, vascular changes quantified by DCE-MRI may show predictive changes earlier than morphological changes seen in standard MRI or CT. 5,41 Based on these results from Spratt et al, the use of multiparametric MRI appears to be the most sensitive imaging technique at detecting response to SSRS and is considered by many to now be the gold standard for monitoring response to treatment. There is currently (at the time of this writing) an ongoing prospective trial evaluating the use of DCE-MRI in the assessment of patients with spinal metastases (NCT02376127; www.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Local control rates of SSRS approach 90% up to 2 years after treatment, 16,60,61 although the accuracy of what is deemed "control" is controversial, given the inability of conventional metrics of tumor size to accurately assess the volume of viable disease and correlate with ultimate tumor progression. 43 There are no standardized consensus guidelines for tumor imaging after SSRS. There are also few studies evaluating the utility of different imaging modalities after SSRS, none of which use histopathological correlation.…”
mentioning
confidence: 99%